2015
DOI: 10.1017/s0033291715000288
|View full text |Cite
|
Sign up to set email alerts
|

The role of the partner and relationship satisfaction on treatment outcome in patients with chronic fatigue syndrome

Abstract: Partners' solicitous responses and illness perceptions at the start of the therapy can negatively affect the outcome of CBT for CFS. We emphasize the importance of addressing this in therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…In patient associations they share experiences, feel understood and uncover their sexual problems. Despite experiencing difficulties [27, 46] and putting women first, our male participants do not lose hope of regaining their sex life. Dissatisfied with their sex life, men seek information and sexology advice [38, 47]; they compensate for sexual dysfunction by strengthening intimacy [22] and fostering new sexual practices [37, 38, 41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patient associations they share experiences, feel understood and uncover their sexual problems. Despite experiencing difficulties [27, 46] and putting women first, our male participants do not lose hope of regaining their sex life. Dissatisfied with their sex life, men seek information and sexology advice [38, 47]; they compensate for sexual dysfunction by strengthening intimacy [22] and fostering new sexual practices [37, 38, 41].…”
Section: Discussionmentioning
confidence: 99%
“…Confronting FSD in FMS requires social and partner support [26]. Women with FMS are supported by their partners in trying to understand the symptoms, seeking information and dealing with the condition, taking responsibility for home duties and childcare [2729].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed a negative influence from solicitous responses of the partner on fatigue and disability. 63 This aspect needs to be included in CBT-programs. The large PACE trial compared CBT with GET, specialist medical care alone and adaptive pacing therapy.…”
Section: Etiopathogenesismentioning
confidence: 99%
“…The second type of response proposed in the review was solicitous significant other responses, such as encouraging patients to rest or doing tasks on their behalf (Cordingley, Wearden, Appleby, & Fisher, ; Kerns & Rosenberg, ). In several studies, solicitous responses have been shown to be associated with increased levels of fatigue severity and disability (Brooks, Daglish, & Wearden, ; Romano et al ., ; Schmaling, Smith, & Buchwald, ) and recently have been linked with poorer patient improvement following cognitive behaviour therapy (CBT; Verspaandonk, Coenders, Bleijenberg, Lobbestael, & Knoop, ). The review proposed that these solicitous responses may promote decreased patient activity (Band et al ., ).…”
Section: Introductionmentioning
confidence: 99%